2019
DOI: 10.1007/s40858-019-00294-z
|View full text |Cite
|
Sign up to set email alerts
|

Survey of begomoviruses and the crinivirus, tomato chlorosis virus, in solanaceous in Southeast/Midwest of Brazil

Abstract: The golden mosaic (begomovirus) and the yellowing (crinivirus) diseases are among the main viral diseases occurring in solanaceous crops in Brazil. A survey of viruses associated with both diseases was conducted on cultivated solanaceous plants from 2013 to 2017 to study their diversity and distribution in the Southeast/Midwest regions of Brazil. Samples from potato, eggplant, sweet pepper and tomato plants were collected in fields of seven Brazilian states (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 38 publications
(38 reference statements)
3
14
0
Order By: Relevance
“…It suggests that after their establishment in a specific crop, under a certain vector population in an intensively cultivated area, the co-existence of two begomoviruses in the same plant is not a common phenomenon. In fact, some regions may have reached this stage with the predominance of ToSRV in the major tomato-growing areas of the country (States of Goiás, São Paulo, and Minas Gerais, Mituti et al, 2019 ), ToMoLCV in the North-East region ( Fernandes et al, 2008 ; Inoue-Nagata et al, 2016 ; Rojas et al, 2018 ), and tomato common mosaic virus (ToCmMV) in the states of Espírito Santo and Rio de Janeiro ( Barbosa et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It suggests that after their establishment in a specific crop, under a certain vector population in an intensively cultivated area, the co-existence of two begomoviruses in the same plant is not a common phenomenon. In fact, some regions may have reached this stage with the predominance of ToSRV in the major tomato-growing areas of the country (States of Goiás, São Paulo, and Minas Gerais, Mituti et al, 2019 ), ToMoLCV in the North-East region ( Fernandes et al, 2008 ; Inoue-Nagata et al, 2016 ; Rojas et al, 2018 ), and tomato common mosaic virus (ToCmMV) in the states of Espírito Santo and Rio de Janeiro ( Barbosa et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, 25 species of tomato-infecting begomoviruses have been described in Brazil (e.g., Flores et al, 1960;Matyis et al, 1975;Ribeiro et al, 2003;Fernandes et al, 2006;Castillo-Urquiza et al, 2008;Fernandes et al, 2008;Albuquerque et al, 2012;Rocha et al, 2013). Bipartite begomoviruses, especially tomato severe rugose virus (ToSRV;Inoue-Nagata et al, 2016;Rojas et al, 2018;Mituti et al, 2019), are the most predominant in tomato plants. The monopartite tomato mottle leaf curl virus (ToMoLCV) (Vu et al, 2015) has also been largely reported in tomato plants and causes severe symptoms such as chlorotic spots, interveinal chlorosis, mottling, mosaic, leaf distortion, and stunting (Inoue-Nagata et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2018, approximately 59.7 thousand hectares were planted to tomatoes in the country, and 4.1 million tons of fruit was produced (Instituto Brasileiro de Geografia e Estatística [IBGE], 2018). Tomato production can be affected by several begomoviruses, the most prevalent being tomato severe rugose virus (ToSRV) (Fernandes et al, 2008;Inoue-Nagata et al, 2016;Rojas et al, 2018;Mituti et al, 2019). Begomoviruses are transmitted by the silverleaf whitefly Bemisia tabaci in a circulative-persistent manner (Rosen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, B. tabaci is responsible for the transmission of begomoviruses and a crinivirus in solanaceous crops, particularly tomato (Inoue‐Nagata et al, 2016). Several species of begomovirus have been reported to infect tomato plants in Brazil; however, a survey between 2013 and 2017 in tomato fields in the states of São Paulo, Minas Gerais, Goiás, Rio de Janeiro, Bahia, and Espírito Santo indicated that tomato severe rugose virus (ToSRV) was prevalent, being detected in 105/136 (77.2%) of plants analysed (Mituti et al, 2019). So far, this begomovirus has been found only in Brazil.…”
Section: Introductionmentioning
confidence: 99%